2007
DOI: 10.1016/j.puhe.2006.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of forest environments on healthy adults: Shinrin-yoku (forest-air bathing, walking) as a possible method of stress reduction

Abstract: This study revealed that forest environments are advantageous with respect to acute emotions, especially among those experiencing chronic stress. Accordingly, shinrin-yoku may be employed as a stress reduction method, and forest environments can be viewed as therapeutic landscapes. Therefore, customary shinrin-yoku may help to decrease the risk of psychosocial stress-related diseases, and evaluation of the long-term effects of shinrin-yoku is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
233
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(266 citation statements)
references
References 36 publications
22
233
1
10
Order By: Relevance
“…Psychological effects of ''Shinrin-yoku'' Morita et al [41] investigated the psychological effects of forest environments with 498 respondents who visited a forest during 4 days of the survey. The survey revealed that the mood of the respondents (hostility, depression, liveliness, and three other positive and negative mood subscales) were significantly improved on the day of the forest visit compared to the control day, when the respondents did not visit a forested area.…”
Section: Field Studies On ''Shinrin-yoku''mentioning
confidence: 99%
“…Psychological effects of ''Shinrin-yoku'' Morita et al [41] investigated the psychological effects of forest environments with 498 respondents who visited a forest during 4 days of the survey. The survey revealed that the mood of the respondents (hostility, depression, liveliness, and three other positive and negative mood subscales) were significantly improved on the day of the forest visit compared to the control day, when the respondents did not visit a forested area.…”
Section: Field Studies On ''Shinrin-yoku''mentioning
confidence: 99%
“…It was found that spending time in a forest can effectively reduce mental stress and alleviate anxiety (Morita et al 2007, Kim et al 2009, Park et al 2011, Ochiai et al 2015, Song et al 2016, Chun et al 2016. This function was recognized as the term of "forest bathing", i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A study to evaluate if Shinrin-yoku (a type of Japanese relaxation therapy where walking or staying in the forest is believed to promote health) has psychological benefits and what factors are associated with these benefits, selected 498 participants who were healthy (Morita et al 2007). Surveys were conducted twice in the forest on the same day and twice on the control day and outcomes were measured using the Multiple Mood Scale Short Form and the State-Trait Anxiety Inventory.…”
Section: Relaxation Restoration and Stress Reductionmentioning
confidence: 99%